PENYELESAIAN PERKARA TINDAK PIDANA PENGANIAYAAN MELALUI KEADILAN RESTORATIF DI CABANG KEJAKSAAN NEGERI PARIGI MOUTONG - Jose Rizal (Fakultas Hukum Universitas Sriwijaya, 2024)
Termination of prosecutions based on restorative justice is a policy established by the Prosecutor's Office as outlined in Prosecutor's Regulation Number 15 of 2020 which supports modern punishment by prioritizing peace and restoration of the original situation. As for the problems taken, what are the obstacles that arise in the application of the principle of restorative justice to the criminal act of persecution in the Parigi Moutong State Prosecutor's Branch and how to apply the principle of restorative justice to the criminal act of persecution in the Parigi Moutong State Prosecutor's Branch in the future The type of research used is Normative-Empirical Research The legal materials in this study consist of primary legal materials, Secondary and Tertiary. From the results of this study, the resolution of cases of criminal acts of persecution can be carried out through Restorative Justice, but it must meet the requirements that have been regulated in the Prosecutor's Regulation of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice, while the obstacles that arise in the application of restorative justice are divided into 2 (two), namely internal barriers and external obstacles, and it is expected that in the future there will be regulations in the future. firmly regulating and accommodating the Implementation of Restorative Justice.